Constituting the Self in Self-determination: an IR approach with an analysis of the Western Sahara case - Barata, Maria João (2022)
Because of the conventional phrasing of the self-determination right in international law, the question of what is “a” people is much debated in politics and literature on self-determination. In addressing this question, the literature on self-determination appears to assume a sequence: first the people, then self-determination. By contrast, in this article, author addresses the problem from an IR perspective, particularly the IR debate on identity, focusing on the role of international norms in making political communities recognizable and legitimate. The author argues that the norm of self-determination influences the constitution of the selves in the international system. The author draws on symbolic interactionism to point out that advancing individuality and originality is always dependent upon society by the mediation of symbolic resources, including norms. The norm of self-determination is a normative resource to project and construct a self that is amenable to perform in the international system and be recognized by others. The self that is proposed by the nationalist movement of the Sahrawi of the Western Sahara—with a delimited territory, a defined population, a collective consciousness and governing structures—illustrates the argument.